2013
DOI: 10.1002/j.2168-0159.2013.tb06326.x
|View full text |Cite
|
Sign up to set email alerts
|

55.2: Ink‐Jet Printed AMOLED Displays Based on High Mobility IGZO TFTs: Cost Does Matter!

Abstract: AMOLED displays based on metal oxide film as active channel layer are fabricated. To achieve cost‐competitive process in OLED manufacturing, solution‐processed HIL, HTL and pixilated EML (RGB) layers followed by evaporation process for other layers are demonstrated in this work. Meanwhile, the AMOLED backplanes possessing low power consumption and high frequency were fabricated on metal oxide TFTs with high mobility (23.13 cm2/Vs) technology. A 14” qHD AMOLED in 79 ppi‐resolution was realized with IGZO based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…For the material development, the solutionprocessable OLED material performance has reached the product level [1][2]. For the panel development, the panel size of a 14-inch and the 65-inch panel were produced by the IJP process [3][4]. For the middle size application, it has been demonstrated that it is possible to produce high resolution displays by IJP [5].…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…For the material development, the solutionprocessable OLED material performance has reached the product level [1][2]. For the panel development, the panel size of a 14-inch and the 65-inch panel were produced by the IJP process [3][4]. For the middle size application, it has been demonstrated that it is possible to produce high resolution displays by IJP [5].…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…The inkjet printing (IJP) process based on solution-processable OLED materials is a very attractive technology because it has a high material usage rate, which allows the process to bring down the material costs for large-size panel fabrication. C. L. Chen et al [1] and P. Y. Chen et al [2] demonstrated good OLED performances in a 14-inch and 65-inch panel produced by the IJP process using oxide thin film transistors (oxide-TFTs) as the backplane. For the media size application, P. Y. Chen et al [3] demonstrated that it is possible to produce high resolution displays despite the limitations in the IJP technique.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…AU Optronics developed high-mobility a-IGZO and a-ITZO backplanes. The latter exhibited an even higher mobility of 33.2 cm 2 /Vs [3,6].…”
Section: Introductionmentioning
confidence: 95%
“…Active matrix displays addressed by a-IGZO TFTs have been demonstrated for LCDs [2] and OLEDs [3]. However, although a-IGZO has a filed effect mobility ( FE ) of ~10 cm 2 /Vs [4], about 10 times larger than that of a-Si, it is insufficient to drive ultra-high definition and high frame rate displays.…”
Section: Introductionmentioning
confidence: 99%